ANALISIS PENGARUH KEPEMILIKAN MANAJEMEN, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN KELUARGA DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN. (Studi Empiris Pada Perusahaan Yang Terdaftar Pada LQ 45 Periode Tahun 2014 – 2017) - Aisyah Nur Baity Sa’diyah; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this research : To test the effect of Management Ownership on Company Values, To examine the effect of Institutional Ownership on Corporate Values, To test the effect of Family Ownership on Company Values, To test the effect of Corporate Social Responsibility on Corporate Values. Research that examines the ownership structure of corporate value has been carried out. But research with family ownership structures is still limited. Therefore research is still needed with family ownership variables. The population of this study were all companies registered in LQ 45 for the period 2014 - 2017. Samples were selected using purposive sampling and there were 39 companies based on criteria. This study uses multiple linear regression models. The results of this study indicate that the concentration of institutional ownership and corporate social responsibility affect the value of the company. The concentration of management ownership and family ownership does not affect the value of the company.Keywords : management ownership, institutional ownership, family ownership, corporate social responsibility and company value